Drug resistance and genetic characteristics of clinical isolates of staphylococci in Myanmar: high prevalence of PVL among methicillin-susceptible Staphylococcus aureus belonging to various sequence types. (March 2016) - Aung, M.S.; Zi, H.; Nwe, K.M.; Maw, W.W.; Aung, M.T.; Min, W.W.; Nyein, N.; Kawaguchiya, M.; Urushibara, N.; Sumi, A.; Kobayashi, N.
Abstract: Prevalence, drug resistance and genetic characteristics were analysed for a total of 128 clinical isolates of staphylococci obtained from a tertiary hospital in Myanmar. The dominant species were S. aureus (39%) and S. haemolyticus (35%), followed by S. epidermidis (6%) and S. saprophyticus (5%). The majority of S. haemolyticus isolates (71.1%) harboured mec A, showing high resistance rates to ampicillin, cephalosporins, erythromycin and levofloxacin, while methicillin-resistant S. aureus (MRSA) was only 8% (four isolates) among S. aureus with type IV SCC mec. Panton-Valentine leukocidin (PVL) genes were detected in 20 isolates of S. aureus (40%), among which only one isolate was MRSA belonging to sequence type (ST) 88/ agr -III/ coa -IIIa, and the other 19 methicillin-susceptible S. aureus (MSSA) isolates were classified into six STs (ST88, ST121, ST1153, ST1155, ST1930, ST3206). An ST1153 MSSA isolate with PVL was revealed to belong to a novel coa type, XIIIa. ST121  S. aureus was the most common in the PVL-positive MSSA (47%, 9/19), harbouring genes of bone sialoprotein and variant of elastin binding protein as a distinctive feature. Although PVL-positive MSSA was susceptible to most of the antimicrobial agents examined, ST1930 isolates were resistant to erythromycin and levofloxacin. ST59 PVL-negative MRSA and MSSA had more resistance genes than other MRSA and PVL-positive MSSA, showing resistance to more antimicrobial agents. This study indicated higher prevalence of mec A associated with multiple drug resistance in S. haemolyticus than in S. aureus, and dissemination of PVL genes to multiple clones of MSSA, with ST121 being dominant, among hospital isolates in Myanmar.